Malignant gastrointestinal melanoma with an unknown primary - Mohan, M.V.T Krishna; Rajappa, Senthil J; Reddy, T Vamshidhar; Paul, T Roshni (Indian Journal of Medical and Paediatric Oncology, 2009)
Malignant melanoma is rare in India; melanoma presenting as a metastatic disease with an unknown primary, involving the gastrointestinal tract without involving lymph nodes is extremely uncommon. We report a case of a 28-year-old male with a malignant melanoma metastasizing to stomach and liver with an unknown primary. Relevant literature is being reviewed.
Keywords: Gastrointestinal; melanoma; unknown primary